Implementation Effectiveness of Water Utilization Permit Grants In Gunung Halimun Salak National Park - Meta, Yonex; Basuni, Sambas; Rusdiana, Omo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Policy implementation is the most difficult stage of the entire policy cycle. The effectiveness of a policy implementation can be measured fromthe accuracy of the implementation, the target, the environment, and the process. The purpose of this research is to analyze the condition and theproblem of implementation of granting Water Utilization Permit (IPA) policy in Gunung Halimun Salak National Park (TNGHS). This research wasconducted in TNGHS area by using closed interview method (questionnaire) followed by in depth interview to key informant which is determined bypurposive sampling, context analysis, and Edward III approach. The results of the research showed that the implementation of granting IPA policy inTNGHS was quite effective because it has been implemented in the right target, environment, and mechanism. However, not all phases have beenimplemented appropriately. Problems encountered include: (a) the use of limited communication strategies, lack of clarity, and inconsistency ofmanagers, (b) limited number of competence counterpart staff and minimal administrative compliance, (c) discretion and disincentive, and (d) tomuch bureaucratic responsibility and lack of implementation guidance or IPA policy SOP. To increase the effectiveness of implementing IPA inTNGHS, some strategies can be added: (a) developing intensive communication and facilitation for Water User Forum (FPA) groups at each resort,(b) providing capacity bulding training as well as additional incentives, (c) rewarding FPAs that implement IPA effectively, and (d) establishingSOPs related to IPA policy.Keywords: effectiveness, implementation, policy